308 Evaluation of Implants and Precision Supplementation on Growth and Muscle Accretion in Beef Steers Post Weaning. (21st September 2022) - Jacobs, Joshua L; Greene, Maslyn A; Udoka, Aliute; Hersom, Matt; Andrae, John G; Duckett, Susan K
Abstract: Backgrounding or stocker operations attempt to add value to calves by efficiently adding weight and predominately taking advantage of the protein accretion phase of development, ultimately preparing calves for later stages of production. The objective of the current study was to evaluate the effects of an implant (Revalor-G) or implant plus supplementation on protein accretion patterns in backgrounded beef steers. A 56-day backgrounding study was conducted using Angus-based steers (n = 69; initial BW 233 ± 29 kg) grazing a cow pea and millet mixture. Steers were randomly assigned to one of three treatments (n = 23 steers per treatment): 1) grazing only (G), 2) grazing with implant (GI), or 3) grazing with implant plus individual animal supplementation via Super Smart Feeder at 0.75% BW (GIS). Steers were weighed and blood was collected every 14 days to determine plasma blood urea nitrogen (BUN) and creatinine concentrations. Ultrasound measurements of ribeye area and backfat were collected at days 0, 28, and 56 of study. Data were analyzed using the GLIMMIX function of SAS version 9.4. GIS steers had a greater (P ≤ 0.0004) body weight change than GI or G steers. GI and GIS steers had a greater (P ≤ 0.0117) ribeye area compared with G steers. GI steers had a greater (P < 0.0180) ribeye area to body weight ratio than G steers. When evaluating blood parameters, GI steers had a greater (P< 0.0009) plasma BUN concentration than GIS steers. No treatment differences were observed for plasma creatinine concentrations. G and GI steers had a greater (P ≤ 0.0290) BUN to creatinine ratio than GIS steers. Results of this study suggest that implanted steers may require additional supplementation to optimize growth and muscle accretion.